Inclusive Strategies: A Qualitative Study of Practices and Perceptions in the English Education Program, Pattimura University - Ferdinandus, Marcy Saartje; Lewier, Christian Albert (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study explores inclusive strategies in English Language Teaching (ELT), focusing on how teachers can effectively address students’ diverse social, cultural, and linguistic backgrounds as well as their varying learning styles and proficiency levels. Grounded in a descriptive qualitative approach, the research draws from literature analysis, document reviews, and previous studies on inclusive pedagogical practices. The findings reveal that differentiated instruction, technology integration, and culturally responsive materials significantly enhance learner engagement, equity, and motivation. Recognizing students’ individual learning preferences—whether visual, auditory, or kinesthetic—enables teachers to design varied activities that support participation and foster confidence. Furthermore, incorporating multicultural and local content in English classrooms promotes cultural awareness and a sense of belonging, particularly in mixed-ability settings and underserved regions such as Indonesia’s 3T areas. Peer and cooperative learning, task differentiation, and adaptive feedback are also found to be effective strategies for bridging learning gaps. These inclusive approaches not only support language development but also nurture intercultural competence, empathy, and collaborative skills essential in global communication. The study concludes that English teachers should adopt empathy-driven, flexible, and culturally sensitive pedagogical approaches to ensure equitable learning opportunities for all learners. Continuous professional development is also recommended to strengthen teachers’ capacity to implement inclusive practices effectively.